(untitled) (Innovative professional education, 2025)
The article explores the role of media literacy as a key factor in shaping communicative culture within the digital educational environment of vocational education. The main issues related to the level of media literacy among educators and learners, as well as the specifics of its integration into the educational process, are analyzed. The significance of media literacy for the development of critical thinking, information security, and the effective use of digital resources is determined. The prospects for improving educational programs through the integration of media literacy across all specializations, the introduction of modern interactive teaching methods, and the development of digital resources for self-directed learning are outlined.